2012
DOI: 10.1111/j.1532-5415.2012.04154.x
|View full text |Cite
|
Sign up to set email alerts
|

Chewing Ability and Tooth Loss: Association with Cognitive Impairment in an Elderly Population Study

Abstract: Sex, age, education, and certain illnesses do not explain the association between cognition and chewing ability. Whether elderly persons chew with natural teeth or prostheses may not contribute significantly to cognitive impairment as long as they have no chewing difficulty. The results add to the evidence of the association between chewing ability and cognitive impairment in elderly persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
191
12
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(238 citation statements)
references
References 31 publications
18
191
12
6
Order By: Relevance
“…Cross sectional population studies [29], have looked at the masticatory ability and oral health of an elderly population and assessed their mental state using the mini-mental state examination (MMSE) to identify those with cognitive impairment, and found that a correlation exists between the two. This pattern of investigation was common across many reports.…”
Section: Human Studies Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross sectional population studies [29], have looked at the masticatory ability and oral health of an elderly population and assessed their mental state using the mini-mental state examination (MMSE) to identify those with cognitive impairment, and found that a correlation exists between the two. This pattern of investigation was common across many reports.…”
Section: Human Studies Measuresmentioning
confidence: 99%
“…The BDNF levels are thought to be higher due to reduced uptake by TrkB, as expression of this receptor is reduced. The exact cause of the reduced TrkB expression is unknown, but various hypotheses are put forward; decreased mastication with the liquid diet leads to a drop in sensory input from the trigeminal and facial nerve to the somatic sensory cortex, or decreased mastication stimulates BDNF expression, and the continuous release of BDNF results in negative feed- Table 2 Results from human studies on mastication and the effects on cognitive function Reference Population Study Outcome [29] >77 years, Swedish population Dental status and chewing difficulty and cognitive function (measured by MMSE)…”
Section: Outcome Of Rodent Studiesmentioning
confidence: 99%
“…In particular, in the elderly person, a decrease in the number of existing teeth due to aging causes a decline in chewing ability, which in turn leads to a decrease in nutrient intake [4] [5]. Associations between chewing ability with activities of daily living (ADL) [6], cognitive function [7], and QOL [8] [9] have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Those who have less than 19 teeth and use no denture are in high risk of falling [29] and that chewing ability is related to problems with activities of daily living (ADL) [30], recognition function [31] and over-all HRQOL [32]. Although there are several reports concerning the relationship between chewing ability and QOL relating to health [33] [34], the relationship between chewing ability and the sleep quality has scarcely been studied.…”
Section: Introductionmentioning
confidence: 99%